Was wissen wir über Betriebsschließungen? Erkenntnisse für West- und Ostdeutschland - Daniel Fackler; Claus Schnabel (Wirtschaftsdienst, 2015)
Schließungen nicht wettbewerbsfähiger Betriebe sind ein wesentliches Element der Marktwirtschaft, werden aber oft kontrovers diskutiert. Wie hoch ist das Risiko einer Betriebsschließung überhaupt und wie hat es sich im Lauf der Zeit entwickelt? Welche Betriebe sind besonders gefährdet? Sterben Betriebe eher einen plötzlichen Tod oder zeichnen sich Betriebsschließungen oft schon Jahre im Voraus ab? – – This paper reports the results of several investigations into the determinants of company shutdowns using administrative data for Germany. We show that between 1975 and 2008, the average shutdown rate has risen considerably in western Germany. For most of the time, shutdown rates in eastern Germany were higher, but they have converged to the western level recently. The shutdown risk falls with company size and is substantially higher for young companies. Shutdown rates initially decline as companies age, reaching a minimum at ages 15 to 18, and then rise again. Companies begin to shrink several years before closure, and the remaining workforce becomes on average more skilled, more female and older in companies about to close compared to surviving ones.
Keywords: D22; J65; L2; 330; Insolvenz; Dauer; Ostdeutschland; Westdeutsche Bundesländer